2014
DOI: 10.1371/journal.pone.0114667
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Combined General-Epidural Anesthesia with General Anesthesia Effects on Survival and Cancer Recurrence: A Meta-Analysis of Retrospective and Prospective Studies

Abstract: ObjectiveAnimals underwent combined general-epidural anesthesia (EGA) is reported to have better long-time outcome than general anesthesia (GA). This study aimed to make overall evaluation of the association between these two anesthetic techniques and prognosis of cancer patients undergoing surgery.MethodsRelated databases such as PubMed and EMbase were searched for eligible studies that evaluated the influence of EGA and GA on the prognosis of cancer patients undergoing surgery. Selected studies were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 32 publications
(37 reference statements)
4
39
2
Order By: Relevance
“…The anaesthetic regimen of epidural anaesthesia combined with general anaesthesia has been reported to exhibit the advantages of maintaining normal hormone levels and requiring less general anaesthetics and/or opioids [9,22], which complies with the case in this study. A recent study [23] revealed that thoracotomy with a thoracic epidural block exerts a decreased impact on postoperative lymphocyte responses compared with surgery performed under general anaesthesia.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The anaesthetic regimen of epidural anaesthesia combined with general anaesthesia has been reported to exhibit the advantages of maintaining normal hormone levels and requiring less general anaesthetics and/or opioids [9,22], which complies with the case in this study. A recent study [23] revealed that thoracotomy with a thoracic epidural block exerts a decreased impact on postoperative lymphocyte responses compared with surgery performed under general anaesthesia.…”
Section: Discussionsupporting
confidence: 87%
“…It has been hypothesized that the anaesthetic management impacts the long-term outcome following surgery, and that an anaesthetic treatment exhibiting low potential for immunosuppression reduces relapse [33]. Pei et al [22] reported that EA may improve the outcome for patients with prostate cancer; they hypothesized that EA is concerned with immunoreaction and oncocytology. The statistical analysis in this study con rmed this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Meta‐analyses for the effect of neuraxial blockade on cancer surgery have generated mixed findings from the heterogeneous and mostly retrospective studies that were included. One concluded that there was no advantage for overall or progression‐free survival (Cakmakkaya et al, ), whereas another suggested there might be a benefit for neuraxial blockade for prostate cancer surgery, but not for colonic cancer (Pei et al, ). The most recent and largest meta‐analysis (incorporating findings from 21 studies) reported an association between improved recurrence‐free and overall survival with neuraxial anaesthesia (compared to general anaesthetic alone), especially in patients having colorectal cancer surgery (Weng et al, ).…”
Section: Systemic Opioid Sparing Surgical Studiesmentioning
confidence: 99%
“…However, the clinical benefit of this combined approach remains unclear. A meta-analysis of studies comparing a technique of combined epidural and general anaesthesia versus general anaesthesia alone failed to convincingly demonstrate a benefit in terms of cancer recurrence [33]. However, in a review of nearly 400,000 patients undergoing hip or knee arthroplasty, whilst the benefit of neuraxial anaesthesia alone was replicated in terms of lesser infection risk any protective effect appeared markedly reduced in the cohort that received a combined general and regional anaesthesia technique [34].…”
Section: Anaesthesia Analgesics and The Inflammatory Responsementioning
confidence: 99%